Complex migration of antibiotic resistance in natural aquatic environments. (January 2018) - Gao, Hui; Zhang, Linxiao; Lu, Zihao; He, Chunming; Li, Qianwei; Na, Guangshui
Abstract: Antibiotic resistance is a worsening global concern, and the environmental behaviors and migration patterns of antibiotic resistance genes (ARGs) have attracted considerable interest. Understanding the long-range transport of ARG pollution is crucial. In this study, we characterized the dynamics of ARG changes after their release into aquatic environments and demonstrated the importance of traditional chemical contaminants in the transmission mechanisms of ARGs. We hypothesized that the main route of ARG proliferation switches from active transmission to passive transmission. This antibiotic-dominated switch is motivated and affected by non-corresponding contaminants. The effect of anthropogenic activities gradually weakens from inland aquatic environments to ocean environments; however, the effect of changes in environmental conditions is enhanced along this gradient. The insights discussed in this study will help to improve the understanding of the distribution and migration of ARG pollution in various aquatic environments, and provide a modern perspective to reveal the effect of corresponding contaminants and non-corresponding contaminants in the process of antibiotic resistance proliferation. Graphical abstract: Highlights: Process of ARGs flow through WWTPs, rivers, estuaries and ocean to implement global proliferation and commutation. The diversity and concentrations of ARGs progressively decrease during dynamic long-range migration processes. The main route of ARG proliferation switches from active transmission to passive transmission from inland to ocean. Abstract : The diversity and concentrations of antibiotic resistance genes progressively decrease during dynamic long-range migration processes.